SIRT1-Dependent Neuroprotection by Resveratrol in TOCP-Induced Spinal Cord Injury: Modulation of ER Stress and Autophagic Flux - Xiangsheng Tian; Yiquan Ou; Shengyuan Shi; Qiuhua Zhou; Sihong Long; Yao Xiang; Weichao Zhao; Dingxin Long (Toxics)
This study explores the neuroprotective effects of resveratrol (Resv) against tri-o-cresyl phosphate (TOCP)-induced neurotoxicity in the spinal cord of adult hens. It is well documented that TOCP exposure causes significant neurodegeneration via mechanisms that involve endoplasmic reticulum (ER) stress and impaired autophagy. In this experiment, adult hens were assigned to one of four groups: Control, Resv, TOCP, and TOCP + Resv. The spinal cord tissues were examined through transmission electron microscopy, hematoxylin and eosin (HE) staining, Nissl staining, and Western blotting to evaluate key proteins associated with ER stress and autophagy. Additionally, RT-qPCR and immunofluorescence were employed to measure sirtuin1 (SIRT1) expression. The findings revealed that TOCP induced severe ultrastructural damage, including disrupted myelin sheaths, dilated ER, and extensive neurodegeneration, as confirmed by histological evaluations. The expression levels of GRP78, p-PERK, p-eIF2α, ATF4, CHOP, Beclin-1, P62, and LC3-II were also significantly elevated by TOCP. However, Resv treatment markedly attenuated these pathological changes by reducing ER stress, restoring autophagic flux, and upregulating SIRT1 expression, preserving spinal cord integrity. These results indicate that Resv can effectively counteract TOCP-induced neurotoxicity by modulating ER stress and autophagy, underscoring its potential as a therapeutic agent for neuroprotection.